The Catholic University of America in the light of norms of canon law - DOMASZK, ARKADIUSZ (Prawo Kanoniczne, 2016)
Universities take a significant part in education of students as well as in scientific researches. Catholic Church also actively participates in the world of science i.e. by running catholic universities. Above study concerns The Catholic University of America, which was founded at the end of 20th century (in 1889). It functioned as a flagship catholic university in the USA. By introducing exactly that university one can understand how the instructions from The Church’s Magisterium and how canon norms apply in practice. The first part of the article analyses norms of canon law concerned with catholic universities, including the term university and its practical applications. Then, it discusses issues concerning the academic community. In the second part of the study it outlines the history of The University in Washington, its present form, and catholic dimension. The university accomplishes objectives typical to university: it educates students, conducts scientific researches, develops skills of teaching staff and cooperates with different research centers. At the same time university evidently preserves catholic nature, which is visible in structural bond between Catholic Church and the university (24 members of Supervisory Board out of 48 seems to be clerics, and from them there are 18 people who belong to United States Conference of Catholic Bishops). The university has three church faculties, which state an excellent bridge between the faith and the mind. Professors receive canonic missions. The catholic dimension of the university is represented by its mission and statute regulations. The mission concerns faithfulness to a Jesus Christ. The university dedicates its activities to develop a bond between the faith and the science. It also reveals truth through scientific researches, and teaching. It remains in service to the Church, American nation, and the whole world. The university places emphasis on involvement of all members of academic community in developing catholic identity of CUA. The university also responds to the expectations from church hierarchy, which regard prospecting and scientific research. The multitude of proposals from university chaplaincy, as well as the university’s commitment in that matter is clearly outlined. The example of described university might be an inspiration to those Polish universities, which are bond with The Catholic Church. It particularly regards a manner of handing canonic mission or mandate down (can. 812). 101 The act of giving mission can be public, during ceremony for the whole of academic community. This kind of method points out a significant relation between the academic teachers, and The Catholic Church. Also it shows the clerical dimension of those faculties. Moreover, the example of university chaplaincy in that particular university, that is: multitude of ideas and structural solutions, could be a reason for Polish universities to search for new ideas in that scope.